Institutional Transformations, Polity and Economic Outcomes : Testing the North-Wallis-Weingast Doorsteps Framework - Quintyn, Marc (IMF Working Papers; Working Paper, 2012)
This paper tests the theoretical framework developed by North, Wallis and Weingast (2009) on the transition from closed to open access societies. They posit that societies need to go through three doorsteps: (i) the establishment of rule of law among elites; (ii) the adoption of perpetually existing organizations; and (iii) the political control of the military. We identify indicators reflecting these doorsteps and graphically test the correlation between them and a set of political and economic variables. Finally, through Identification through Heteroskedasticity we test these relationships econometrically. The paper broadly confirms the logic behind the doorsteps as necessary steps in the transition to open access societies. The doorsteps influence economic and political processes, as well as each other, with varying intensity. We also identify income inequality as a potentially important force leading to social change.